In-situ monitoring of production of large composite structures using tool embedded capacitors - Levadoux, Galatée P. (2019)
The development of a new coplanar dielectric sensor able to monitor the entire process used for the manufacture of large composites panels was the main focus of this study. The cure reaction of an industrially available epoxy resin was investigated using differential scanning calorimetry and dynamic viscometry. A kinetics model of the resin cure was proposed for both constant heating rates and isothermal conditions. The theory of dielectric monitoring was outlined and electrical equivalent circuit were used in order to model the variations of the admittance due to the microscopic behaviour of the resin during cure. Electrical circuit equivalents were similarly used to model the variations of the sensor admittance during the filling of an infusion mould with liquid resin. Several dielectric sensor prototypes were built in order to validate the geometry and fabrication protocol of the final prototype. These sensors were used to collect the variations of admittance in a frequency range of 1 Hz - 10 kHz during the infusion of glycerol, the infusion of unreinforced epoxy resin and the cure of the said resin. The results obtained with the first prototypes confirmed the chosen geometry and structure of the sensor was suitable to follow the infusion and cure of epoxy resin. A first attempt at 3D modelling of the sensor was carried out. A final prototype of flexible and reusable dielectric sensor was built and used to monitor the infusion and cure of unreinforced epoxy resin, as well as the infusion and cure of glass fibre/epoxy composite plates in a frequency range of 1 Hz – 10 kHz. The results obtained confirmed the prototype was able to follow the filling of an infusion mould in two dimensions, as well as the cure of glass fibre/epoxy composite plates on a scale of centimetres. The influence of the number of reinforcement layers on the admittance measured was found inexistent. The admittance obtained during the epoxy resin cure confirmed the prevalence of the migrating charges contribution to the resin admittance in the frequency range studied. The comparison of the results obtained with the resin characterisation data suggested a way to closely follow the cure near the gel point of the resin.